SMART accelerates rate of cognitive gains in service members with mTBI and PTSD - Venza, Erin; Spence, Jeffrey S.; Zientz, Jennifer; Devlin, Cole; Bailie, Jason; Darr, Andrew; Babakhanyan, Ida; Chapman, Sandra Bond (Frontiers in Human Neuroscience, 2025)
IntroductionThis randomized clinical trial (RCT) compared the efficacy of two cognitive rehabilitation (CR) protocols—Strategic Memory Advanced Reasoning Training (SMART) and Study of Cognitive Rehabilitation Effectiveness (SCORE)—in improving higher-order cognitive functions among active-duty service members (ADSMs) with mild traumatic brain injury (mTBI) and varying levels of post-traumatic stress disorder (PTSD) symptoms. The study also examined the relationship between PTSD symptom severity and cognitive outcomes.MethodsA total of 148 ADSMs with mTBI and persistent cognitive complaints were randomized to receive either SMART (20 h over 4 weeks) or SCORE (60 h over 6 weeks). High-level cognitive abilities were assessed with the Test of Strategic Learning and the Visual Selective Learning Task, and PTSD symptoms were measured using the PTSD Checklist (PCL-M). PTSD symptoms were accounted for as a covariate in all analyses. Outcomes were measured at baseline, post-treatment, and at 3-month follow-up.ResultsBoth SMART and SCORE groups showed significant improvements in complex memory and strategic learning, with no between-group differences in overall cognitive gains. Notably, SMART participants achieved these outcomes in one-third of the treatment hours. SMART also demonstrated greater immediate gains in fluency of high-level interpretations compared to SCORE (p = 0.04), reflecting enhanced possibility thinking. PTSD symptom severity was negatively correlated with performance on cognitive measures; however, the cognitive gains were comparable regardless of baseline PTSD symptoms.DiscussionSMART is an efficient and effective CR protocol for improving higher-order cognitive abilities in ADSMs with mTBI, achieving comparable outcomes to SCORE in 60% fewer treatment hours. Also of note, training-based cognitive gains were consistent across PTSD severity levels, suggesting CR is a potentially reliable tool for populations with mTBI plus concomitant PTSD. By promoting rapid cognitive improvement and adaptability, this study supports the potential for SMART to enhance the operational readiness of warfighters. Future research should explore hybrid delivery models and integration with PTSD-focused interventions to optimize accessibility and outcomes.